Minimalism and beyond : radicalizing the interfaces - Kosta, P. (Peter); Franks, Steven; Radeva-Bork, Teodora; Schürcks, Lilia (Language faculty and beyond, 2014)
The problem pursued in this paper concerns the role of Arbitrariness in linguistic expressions. Saussurean Arbitrariness is due to the conventional sound-meaning-relation of linguistic expressions. It is systematically projected (but not reduced) from Lexical Items to linguistic expressions of unrestricted complexity by the operation of Merge. This raises the question, whether this arbitrariness is an incidental byproduct of the systems complexity, which could be avoided under conditions of optimal design. With this perspective, language is compared to mental systems of comparable complexity,